Coming of age in women artistic gymnastics: The influence of rules on career development - Nunomura, M.; Barker-Ruchti, N.; Schubring, A.; Kerr, R.; Cervin, G.; Marques, R. F. R. (12th EASS conference, 10-13 June 2015, 2015)
Age has long been debated in women`s artistic gymnastics (WAG). Since the 1970s, young gymnasts with pre-pubescent physiques and extreme levels of performance tend to dominate the sport. Growing critique of the problematic side-effects of this trend led the International Gymnastics Federation (FIG) to introduce the minimum age limit of 16 for international competitions in 1996. Since then, the FIG has implemented further changes through their rules book the Code of Points, which have implications for gymnasts` career development. In drawing on results from an interview study with more than 20 internationally successful gymnasts who are/were over the age of 20 when competing, as well as coaches and judges, this presentation discusses the impact of the Code of Points on career development. The findings demonstrate that on the one hand, stakeholders spoke of how the Code of Points related to gymnasts extending their career into their twenties. In particular, the changes towards artistry are important criteria that interviewees related to career continuation. On the other hand, the increased difficulty requirements since the beginning of 2000 continue to place enormous pressures on gymnasts to train intensely from a young age. The physical demands and the risk for injuries detriment gymnasts` career prolongation. We conclude that although the FIG has made some efforts to encourage the presence of older gymnasts, these have only been semi-successful, with a younger, pre-pubescent body still viewed as ideal for WAG.